2015
DOI: 10.3897/compcytogen.v9i4.5741
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic description of the earthworm Drawida ghilarovi Gates, 1969 (Oligochaeta, Moniligastridae) from the southern Russian Far East

Abstract: Sixty-six specimens of the earthworm Drawida ghilarovi Gates, 1969 (Oligochaeta, Moniligastridae) from 15 localities of the southern Russian Far East were studied cytogenetically. We examined chromosome sets during mitosis and diakinesis as well as DNA content in the spermatogenous and somatic cell nuclei. The populations and morphs displayed no differences in karyotype and ploidy levels estimated in terms of both chromosome number and DNA mass index: n = 10, 2n = 20; c = 1.1 pg, 2c = 2.2 pg. We conclude that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…on the northernmost distribution limits have been performed. Anisimov et al (2015) stated the chromosome number, DNA mass index and concluded that polyploidy as a species-or race-forming factor is not typical of these earthworms. Studies of mitochondrial COI gene fragment variations (Atopkin & Ganin 2015;Ganin & Atopkin 2018) have revealed differences between meadow-swampy D. sp.nov and forest D. ghilarovi for 15-17%.…”
Section: Introductionmentioning
confidence: 99%
“…on the northernmost distribution limits have been performed. Anisimov et al (2015) stated the chromosome number, DNA mass index and concluded that polyploidy as a species-or race-forming factor is not typical of these earthworms. Studies of mitochondrial COI gene fragment variations (Atopkin & Ganin 2015;Ganin & Atopkin 2018) have revealed differences between meadow-swampy D. sp.nov and forest D. ghilarovi for 15-17%.…”
Section: Introductionmentioning
confidence: 99%